An online platform for conducting spatial-statistical analyses of national census data across Australia. (May 2017) - Pettit, Christopher J.; Tanton, Robert; Hunter, Jane
Abstract: In recent years there have been significant advances in online planning and decision support systems that encompass spatial and statistical analysis and visualisation services. In this paper we provide an analysis and evaluation of one particular online spatial-statistical platform, known as the Australian Urban Research Infrastructure Network (AURIN) portal. By adopting the Statistical Data and Metadata Exchange (SMDX) format, more than 500 socio-economic data products can be dynamically searched, browsed, accessed and analysed via the AURIN portal. The significance of this approach is that urban geographers can access both the datasets and statistical analysis tools via the same online Portal and thus in theory, conduct their research more efficiently. In conducting our research we specifically focus on three practical use cases which utilise machine-to-machine access from the AURIN portal to the national census data maintained by the Australian Bureau of Statistics (ABS). The first use case involves location quotient analysis in New South Wales to analyse the financial sector. The second use case focuses on understanding economic growth across industry sectors across Queensland using shift-share analysis. The third use case aims to identify spatial autocorrelation between low income and other spatial variables in South Australia. Through this in-depth case study approach we have identified there are some strengths and weaknesses with the AURIN portal. We have demonstrated that the portal can successfully search, interrogate and visualise spatial-statistical data from across Australia. We have also demonstrated that the AURIN portal can successfully conduct simple spatial-statistical analysis all via a single online platform. However, we have also found there remains significant challenges in manipulating and visualising complex multi-dimensional datasets through the portal. Yet these challenges are not considered insurmountable and further research should endeavour to address them. In conclusion, it is important to highlight that online platforms such as the AURIN portal hold significant promise as effective planning and decision support systems which can be used to better shape our cities. Highlights: Open data made available via web services is a powerful enabler of advanced spatial analysis. The AURIN Portal has enabled researchers to access, analyse, and visualise ABS Census data via a single online platform. This research endeavours to inform the design of the next generation of online spatial planning and decision support systems. Visualising and manipulating multi-dimensional statistical data remains a challenge.